1981
DOI: 10.1007/bf02425446
|View full text |Cite
|
Sign up to set email alerts
|

Glycophorin A in phosphatidylcholine bilayer membranes

Abstract: Glycophorin A is one of the major integral proteins in erythrocyte membranes. We will report on the reconstitution of Glycophorin A into artificial phosphatidylcholine membranes (DMPC) in the concentration range between O,i and i0 mol %o proteins. The influence of the protein on the structure and the dynamics of the lipid matrix has been investigated by the following techniques: i) Electron paramagnetic resonance (EPR) and calorimetry (DTA).We observed a slight shift of the main phase transition temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

1983
1983
1995
1995

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 0 publications
2
17
0
Order By: Relevance
“…Glycophorin was chosen in the present work as an example of a membrane-spanning species with extensive carbohydrate (Marchesi et al, 1976). Bilayers containing glycophorin have been extensively characterized by us and other workers (Ketis & Grant, 1980;Ruppel et al, 1982; Grant & Peters 1984; MacDonald & Pink, 1987), and it is known to distribute uniformly as small oligomers in such systems. Glycophorin A is a 30 kDa integral membrane protein that contains 16 (-)-charged oligosaccharide chains (Vítala & Jamefelt, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Glycophorin was chosen in the present work as an example of a membrane-spanning species with extensive carbohydrate (Marchesi et al, 1976). Bilayers containing glycophorin have been extensively characterized by us and other workers (Ketis & Grant, 1980;Ruppel et al, 1982; Grant & Peters 1984; MacDonald & Pink, 1987), and it is known to distribute uniformly as small oligomers in such systems. Glycophorin A is a 30 kDa integral membrane protein that contains 16 (-)-charged oligosaccharide chains (Vítala & Jamefelt, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…One observes + 1 disclinations with point-like cores, but -1 disclinations always exhibit lines like cores. c) Addition of 0.2 %0 glycophorine A (for a general information about this protein and its interaction with lipids see for example [23]). The protein is preferentially accumulated in the point and line defects.…”
Section: Induced Defects In the Fluid L-phase -mentioning
confidence: 99%
“…Since these packing defects result in a permeability increase for much smaller solutes [ 151 we favour the idea that the permeation of solutes through the glycophorin-DOPC bilayer occurs through channels, formed by glycophorin aggregates. Recently it was suggested that the sugar-containing externally located part of glycophorin may interact with the phospholipid bilayer [22]. Possibly this interaction may play a role in the formation of the permeation pathway, present in the glycophorin-DOPC vesicles.…”
Section: Resultsmentioning
confidence: 99%